Lowest White Boy - Bottoms, Greg (Book collections on Project MUSE., 2019)
"An innovative, hybrid work of literary nonfiction, Lowest White Boy takes its title from Lyndon Johnson's observation during the civil rights era: "If you can convince the lowest white man he's better than the best colored man, he won't notice you're picking his pocket." Greg Bottoms writes about growing up white and working class in Tidewater, Virginia, during school desegregation in the 1970s. He offers brief stories that accumulate to reveal the everyday experience of living inside complex, systematic racism that is often invisible to economically and politically disenfranchised white southerners--people who have benefitted from racism in material ways while being damaged by it, he suggests, psychologically and spiritually. Placing personal memories against a backdrop of documentary photography, social history, and cultural critique, Lowest White Boy explores normalized racial animus and reactionary white identity politics, particularly as these are collected and processed in the mind of a child."--Provided by publisher